Gap quality of employee attendance system application using technology acceptance model approach and fuzzy - Herman Ruswan Suwarman; Rina Indrayani (The Management Journal of Binaniaga, 2019)
The employee attendance system application in an educational institution occupies an important role in providing evaluation and improving performance in addition to being able to improve the transparency of employee and institutional relations. In its use, the employee attendance system must be able to accommodate the needs of its users, namely employees and staffing. This research evaluates user satisfaction over system applications using the Technology Acceptance Model approach. The evaluation was conducted by assessing the level of perception and satisfaction level of 40 users, in this case, employees. The research variable used is perceived usefulness, perceived ease of use (level of ease of use received), and user satisfaction (level of user satisfaction). Computing process was done by fuzzy methods. The results showed that some quality of the application could not meet the expectations of employees at this time. The only variable that met the performance and expectation was perceived ease. Key Words : TAM, Employee Attendance System Aplication, GAP Nad Fuzzy Method